Sosialiasi Dokumentasi Dijital Virtual Reality Masjid Pathok Negoro Wonokromo - Hendro Trieddiantoro Putro; Endang Setyawati (Jurnal ABDI RAKYAT, 2024)
Through this activity, socialization of digital documentation has been carried out to community members at the Pathok Negoro Wonokromo mosque. Then, digital documentation of Virtual Reality was displayed, and questionnaires were filled out by 67 residents as an assessment and evaluation of the socialization of digital documentation at the Pathok Negoro Wonokromo mosque. The results of the questionnaire show that most people have known the Pathok Negoro Wonokromo mosque since childhood and agree that the Pathok Negoro Wonokromo mosque is the identity of the Islamic community, Javanese society, and is a symbol of the glory of the Sultanate of Yogyakarta. The community also agreed that through digital documentation that was broadcast, it had provided information about the culture and history of the Pathok Negoro Wonokromo Mosque. However, the community considers that the building details, colors, and details in the digital documentation that is broadcast need to be adjusted again to the conditions of the Pathok Negoro Wonokromo mosque. In addition, the results of the questionnaire also show that the community does not agree if the Pathok Negoro mosque is changed to a modern mosque.